Application of a Remote Lab: Single Phase PFC circuit - Akin, Burak (International Journal of Online and Biomedical Engineering (iJOE), 2006)
Some universities may not have enough resources to provide each student with a separate device in the laboratory. When the number of students in the experiment exceeds the number of devices, then the experiment is carried out by some of the students only while the rest remains indifferent to the experiment. Therefore, not all the students can benefit from the experiment. Nowadays remote laboratory and its applications are being very popular by young scientists and undergraduate students who are willing to learn and research in different topics of their interests. Web and computer are two fundamental tools for this kind of education. In this paper, matlab simulation of single phase PFC is being presented as a remote laboratory application for the students.